A new ultraluminous X-ray source in the galaxy NGC 5907. (24th March 2018) - Pintore, F; Belfiore, A; Novara, G; Salvaterra, R; Marelli, M; De Luca, A; Rigoselli, M; Israel, G; Rodriguez, G; Mereghetti, S; Wolter, A; Walton, D J; et al.
Abstract: We report on the serendipitous discovery of a new transient in NGC 5907, at a peak luminosity of 6.4 × 10 39   erg s −1 . The source was undetected in previous 2012 Chandra observations with a 3σ upper limit on the luminosity of 1.5 × 10 38  erg s −1, implying a flux increase of a factor of >35. We analysed three recent 60 ks/50 ks Chandra and 50 ks XMM–Newton observations, as well as all the available Swift/XRT observations performed between 2017 August and 2018 March. Until the first half of 2017 October, Swift/XRT observations did not show any emission from the source. The transient entered the ultraluminous X-ray source (ULX) regime in less than two weeks and its outburst was still on-going at the end of 2018 February. The 0.3–10 keV spectrum is consistent with a single multicolour blackbody disc ( kT  ∼ 1.5 keV). The source might be an ∼30 M⊙ black hole accreting at the Eddington limit. However, although we did not find evidence of pulsations, we cannot rule out the possibility that this ULX hosts an accreting NS.